UPAYA PEMBIMBING DALAM MEMBINA ANAK ASUH DI PANTI SOSIAL BINA GRAHITA HARAPAN IBU KALUMBUK PADANG. - -, Hanifandi - (Bimbingan dan Konseling, 2014)
This research is motivated by the constraints experienced tutors in fostering mentally disabled foster children in the mild and moderate Panti Sosial Bina Grahita Harapan Ibu Kalumbuk Padang. This aims to describe: 1) efforts made in developing counselor mild mentally disabled children, 2) the efforts made in developing counselor mentally disabled children were. This research was conducted with a qualitative descriptive approach is, that describes the symptoms, facts and reality in the field what it is about the effort in fostering mentor foster children. The informants were: mentor, head panti and head kasi. The instrument used in this study were interviews. Data processing techniques are data reduction, data presentation and conclusion. The results of the interviews have been analyzed revealed that 1) efforts in fostering a child counselor tuna grahita light. In speaking, in a way that is easily understood as sign language, in terms of placement assessment assessment to see where lies the childs wishes and given the availability of special programs for childrens independence. 2) guidance in their efforts to foster children tuna grahita moderate. In terms of easy to understand language like sign language and pointed directly in directing, in terms of placement of the child should be assessed to see where the location assessment of aptitude and interest to be channeled in a skill area and the availability of special programs, should be given to the childs independence as coach children continuously and repeatedly.